ALK-rearranged lung adenocarcinoma transformation into high-grade large cell neuroendocrine carcinoma: Clinical and molecular description of two cases. (August 2020) - Fares, Aline F.; Lok, Benjamin H.; Zhang, Tong; Cabanero, Michael; Lau, Sally C.M.; Stockley, Tracy; Patel, Devalben; Bradbury, Penelope A.; Sacher, Adrian; Yasufuku, Kazuhiro; Morash, Barbara A.; Sabatini, Peter J.B.; et al.
Highlights: First two cases of ALK -rearranged LUAD that transformed to high-grade LCNEC after ALK-TKI treatment. Development of on-target ALK G1202R mutation, showing unique dual mechanisms of resistance in both cases. Different RB1 status in both cases, with worse outcome in the case with RB1 loss.